Political commitment and beneficiary attitudes on free nutritious meals program - Winanta, Rizza Arge; Putri, Wahyu Eka; Safitri, Baiq Vira; Prawira, R. Yogie (Jurnal Kajian Komunikasi, 2026)
Background: The Indonesian government has exhibited a strong political commitment to the Free Nutritious Meals Program (locally known as MBG - Makan Bergizi Gratis), which targets the enhancement of nutrition, reduction of stunting, and stimulation of economic growth. Purpose: To investigate the impact of political commitment (expressed and institutional commitment) on the attitudes of beneficiary students in rural and small urban areas of Central Java. Methods: An explanatory quantitative survey was conducted with 413 junior and senior high school students who were beneficiaries of the Free Nutritious Meals Program. Results: The findings reveal that political commitment positively influences the attitudes of the beneficiary students. Expressed commitment (β = 0.364, p < 0.001) and institutional commitment (β = 0.410, p < 0.001) exert a significant positive influence on student attitudes, with institutional commitment emerging as the predominant predictor. The model accounts for 48.5% of the variance in attitudes. Conclusion: Constant vocal support by political leaders, together with their specific policy, regulatory, and infrastructure plans, could develop a positive perception among beneficiaries. The research establishes political dedication as a factor that determines public perception of national programs, which affects rural and small urban communities. Implications: Policymakers should be advised to further fortify their verbal commitments by widely communicating their intent so that their program can be best understood. Institutional commitment must be strengthened to ensure the program’s sustainability and effectiveness. Further research applying a qualitative approach is recommended to obtain subjective perspectives and augment the understanding of social acceptance of the Free Nutritious Meal Program.